What is the precise role of cognitive control in the development of a sense of number? - Merkley, R; Scerif, G; Ansari, D (Cambridge University Press, 2017)
The theory put forward by Leibovich et al. of how children acquire a sense of number does not specify the mechanisms through which cognitive control plays a role in this process. We argue that visual attention and number word knowledge influence each other over development and contribute to the development of the concept of number.